Multilocal living and spatial development. - Danielzyk, Rainer; Dittrich-Wesbuer, Andrea; Duchêne-Lacroix, Cédric; Fischer, Tatjana; Hilti, Nicola; Perlik, Manfred; Petzold, Knut; Ritzinger, Anne; Scheiner, Joachim; Sturm, Gabriele; Wesike, Christine (My University, 2021)
In this position paper, the "Multilocal living and spatial development’"Working Group at the Academy for Territorial Development (ARL) discusses a current social phenomenon that has spatial implications at various levels: multilocal living arrangements, i.e. the practice of living alternately at different locations. Increasing numbers of people live at more than one location and establish spaces for their everyday activities at each location (residential multilocality).
Keywords: Wohnstandort; Arbeitsort; Zweitwohnung; Zweitwohnsitz; Berufspendler; Raumwirksamkeit; Wirkungsanalyse; Regionalentwicklung; Multilokalität